PENGEMBANGAN MEDIA PEMBELAJARAN BAHASA INGGRIS MATERI POKOK VOCABULARY UNTUK SISWA KELAS V SDN 298 CABALU BERBASIS MACROMEDIA FLASH 8 - darnilah darnilah; Raden Wirawan; Muh Awal Nur (Institut Teknologi dan Bisnis Bina Adinata, 2025)
The result of this research is (1) design stage English learning media vocabulary subject matter in grade V students of SDN 298 Cabalu, development method, namely the multimedia development life cycle (MDLC). This research aims to develop a more interesting and efficient learning so that it namely with the input design stage, namely Unified Modeling Language (UML), namely, use case diagrams, activity diagrams, sequence diagrams and statechart diagrams as well as output design using macromedia flash 8 software. (2)This mathematics learning media is implmented to grade V students of SDN 298 wich can be used in the learning procces as a new learning medium and has been validated with the results of the blackbox test and all buttons or icons work according to their functions. (3)The students learning motivation when using English learning media, the subject matter of vocabulary for class V SDN 298 Cabalu, is in the “MEDIUM” category, while after using learning media the level of learning is in the “HIGH” category. This can be seen from the average score of learning motivation before the use of learning media is “27,33” and after use of learning media the average score of student learning motivation is “46,73”